R‐Ras deficiency does not affect papain‐induced IgE production in mice - Kummola, Laura (Immun Inflamm Dis, 2017)
INTRODUCTION: R‐Ras GTPase has recently been implicated in the regulation of immune functions, particularly in dendritic cell (DC) maturation, immune synapse formation, and subsequent T cell responses. METHODS: Here, we investigated the role of R‐Ras in allergen‐induced immune response (type 2 immune response) in Rras deficient (R‐Ras KO) and wild type (WT) mice. RESULTS: Initially, we found that the number of conventional DC's in the lymph nodes (LNs) was reduced in R‐Ras KO mice. The expression of co‐stimulatory CD80 and CD86 molecules on these cells was also reduced on DC's from the R‐Ras KO mice. However, there was no difference in papain‐induced immune response between the R‐Ras WT and KO as measured by serum IgE levels after the immunization. Interestingly, neither the DC number nor co‐stimulatory molecule expression was different between WT and R‐Ras KO animals after the immunization. CONCLUSIONS: Taken together, despite having reduced number of conventional DC's in the R‐Ras KO mice and low expression of CD80 on DC's, the R‐Ras KO mice are capable of mounting papain‐induced IgE responses comparable to that of the WT mice. To our knowledge, this is the first report addressing potential differences in in vivo allergen responses regulated by the R‐Ras GTPase.